Primary numerical study of the wave current interaction in river mouth regions - Ninh, Pham Van; Quynh, Do Ngoc; Manh, Dinh Van (Vietnam Journal of Mechanics, 1995)
A hydro-numerical model based on the nonlinear shallow water equation system has been developed for calculation of the surface wave picture in river mouth regions. In the model the river flow ants the sea surface wave have been given at some river cross-section and at a deep sea boundary respectively and the real topography, wind and bottom friction stresses, orioles force also are taken into account. Calculated results for various river flows and sea waves with a simple river mouth topography show that the model can be used for studying interaction between waves and river currents in interesting areas.